Pengaruh Pemberian Edukasi Kepatuhan Konsumsi Tablet Tambah Darah (TTD) terhadap Peningkatan Pengetahuan dan Sikap Remaja Putri dan Orang Tua di Kabupaten Bangkalan - Yufuria Christiansi, Welldelin; Indriani, Diah; Salsabilla, Nendy Putra; Oktaviana, Riska; Afianto, Rery; Yan Mario Paridy Man, Giovanny; Iitdrie, Iitdrie; Ayu Prasetya Astuti, Aldiella; Zahrotul Adha, Aziza; Hardianti, Sri; Nurhayati, Aprillia; Arina Pambudi, Tesalonika (UI Scholars Hub, 2025)
Background. The results of the Indonesian Health Survey (SKI) in 2023 showed that the prevalence of anaemia in adolescents was 14.6%. Knowledge about blood tablets is one of the factors that can influence someone’s blood tablets consumption behavior. Increasing knowledge and attitudes regarding blood tablets consumption can be done through education. Aim. This study aims to analyse the effect of providing education on improving the knowledge and attitudes of parents and adolescent girls regarding anaemia prevention and consumption of blood supplement tablets in Socahah District, Bangkalan Regency. Method. This study used a quasi-experimental design by designing one group pre-test and post-test. The pre-test was conducted before the anemia prevention education. The post-test was conducted seven days after the training involving 89 adolescent girls aged 12-15 years and 40 parents in 3 junior high schools in Socah sub-district, Bangkalan district. Data were collected using validated questionnaires and analysed using the Wilcoxon test to measure changes in knowledge and attitudes. Result. Adolescent knowledge increased from 22.4% to 44.9% (p=0.00), as did attitudes which increased from 30.0% to 51.6% (p=0.00). In parents, there was a very significant increase in knowledge from 42.5% to 82.5% (p = 0.00), as well as an increase in attitude that reached 100% (p = 0.00). There was no effect of providing education in improving parental support in the prevention of anaemia and the importance of taking blood supplement tablets for adolescents (p = 0.45).